Targeting mitophagy in diabetic retinopathy: novel insights into SQSTM1/BNIP3L pathway regulated by luteolin - Zhang, Shuyan; Wu, Jiajun; Zhang, Yinjian (Frontiers in Pharmacology, 2025)
ObjectiveDiabetic retinopathy (DR) is a leading microvascular complication of diabetes. Luteolin, a flavonoid with known anti-inflammatory and antioxidant properties, has demonstrated therapeutic potential in early investigations for the treatment of DR. However, its precise molecular mechanisms remain inadequately defined. This study aimed to explore the local and systemic immunological mechanisms underlying luteolin’s therapeutic effects on DR.MethodsKey regulatory genes and cell subpopulations were identified from single-cell RNA sequencing (scRNA-Seq) datasets derived from peripheral blood mononuclear cells (PBMCs) and retinal tissues of DR patients. The molecular interactions were analyzed using molecular docking simulations. Reactive oxygen species (ROS) were quantified through DCFDA assays, while retinal structural damage was assessed using Hematoxylin and eosin (H&E) and Periodic Acid-Schiff (PAS) staining. Comprehensive analyses, including enzyme-linked immunosorbent assays (ELISA), immunofluorescence, immunohistochemistry, and Western blotting were conducted to evaluate cytokine levels and protein expression.ResultsThe study revealed that luteolin exerted protective effects against DR primarily by activating mitophagy and reducing oxidative stress, with the SQSTM1/BNIP3L pathway emerging as a critical mediator. Furthermore, a novel mechanistic link was established between monocyte activity and DR progression, highlighting the VISFATIN signaling pathway’s role in immune cell regulation and its contribution to disease pathology.ConclusionThis study offers novel insights into the luteolin’s therapeutic potential in DR, particularly activating mitophagy through the SQSTM1/BNIP3L axis, which expands the scope of natural compounds in addressing this sight-threatening complication of diabetes.